Magnetic behaviour of Ce(Pd1-xMx) compounds (M = Rh, Ni and Ag) within the LDA approximation - Vildosola, V.L. (2001)
Fil: Vildosola, V.L. Comisión Nacional de Energía Atómica; Argentina; Universidad de Buenos Aires; Argentina